Utility of next generation sequencing to unequivocally establish clonality in synchronous vs metastatic endometrial and ovarian carcinomas - Michelle Greenman; Stefania Bellone; Tobias Hartwich; Natalia Buza; Alessandro D. Santin (Elsevier, 2024)
Background: Synchronous endometrial and ovarian carcinomas represent up to 10% of all endometrial and ovarian tumors. These are diagnostically challenging cases to determine if they represent dual primary tumors or related metastatic tumors. Case: A 48-year-old was diagnosed with synchronous primary ovarian and endometrial malignancies on pathology based on traditional morphological parameters. However, following next generation sequencing (NGS) of tumors from both the uterus and ovary, the malignancies were unequivocally recognized as primary uterine tumor metastatic to the ovary using mismatch repair protein expression profile and tumor clonality. Conclusion: NGS using FDA-approved commercially available platforms is becoming increasingly utilized to understand the genetic landscape of tumors and select the appropriate targeted therapies for improved outcomes. Simultaneous sequencing of synchronous endometrial and ovarian carcinomas may represent the new gold standard to unequivocally demonstrate tumor clonal relationships, properly classify disease as well as guide the most appropriate adjuvant treatment in these challenging cases.